Dalihan Na Tolu dalam Perspektif Eskatologi dan Relevansinya Bagi Misi Gereja Katolik - Martina Rosmaulina Marbun; Rikki Makkirap Simamora; Kristiana Liliejeri Lase; Cahyaningsih Paskalia Humendru; Sabar Berkat Hulu; Atanasius Zai; Bonifasius Gulo (CV. ALIM'SPUBLISHING, 2026)
This research aims to examine the values contained in Dalihan Na Tolu through the perspective of Christian eschatology and examine its relevance to the mission of the Catholic Church in society. Dalihan Na Tolu as a socio-cultural system of the Batak community contains the values of respect, solidarity, responsibility, and brotherhood which play an important role in building social harmony. This research uses a qualitative method with a library research approach through the collection of data from various books, journals, Church documents, and scientific sources relevant to the research theme. The results of the study show that the values in Dalihan Na Tolu are related to eschatological expectations in the Christian faith, especially in building a life that reflects the love, brotherhood, and fellowship that God wills. In addition, Dalihan Na Tolu also has relevance in the Church's mission as a means of inculturation in the proclamation of the Gospel that is more contextual in the Batak community. Thus, local culture is not seen as an obstacle to faith, but rather as a means that can support the realization of the values of God's Kingdom in common life.